Efeitos de estatinas sobre a cetonemia, glicemia e lipidemia - Rodrigues, Maria Cláudia Cândida (2008)
Statins depress cholesterologenesis, enhancing the levels of acetyl-CoA, which according the mass action law could exacerbate ketogenesis and inhibit pyruvate dehydrogenase, with a decrease of glucolysis. The aim of this work was to investigate the effects of the statins use on the blood levels of glucose and ketone bodies in normoglycemic patients. The study population consisted of 9 patients who received prescription for statin use (40 mg/day of simvastatin or 10 mg/day of atorvastatin). The blood levels of β-hydroxy-butyrate, total cholesterol, LDL-cholesterol, HDL-cholesterol, VLDL-cholesterol, triglycerides and glucose were determined on the day preceding the beginning and at the 15, 30, 45 and 60 days of treatment. There was no disturbance of ketonemia during treatment. The levels of total cholesterol and LDL-cholesterol dropped at the 15th day, but subsequently have remained unchanged. The levels of HDLcholesterol were increased modestly but significantly at the 60th day of treatment. The levels of VLDL-cholesterol and triglycerides declined significantly at the 30th day, but subsequently remained unchanged. The blood glucose increased at the 15th day, but declined again at the 60th day of treatment. The use of statins for a period of 60 days not upset the ketonemia but caused transient elevation in the blood glucose levels.